Wacana Multimodal Pada Billboard Bacapres 2024 - Rudi Haryatno, Yulius (Jurnal Industri Kreatif dan Inovatif, 2023)
One of the visual displays that has attracted the attention of the public and Indonesian political observers aheadof the 2024 presidential election (Pilpres) is the billboard for presidential candidates (Bacapres) PrabowoSubianto (PS) and Ganjar Pranowo (GP), each of whom is side by side with President Jokowi Dodo. OnlyBacapres Anies Baswedan (AB) did not display the figure of President Joko Widodo on his billboards or politicaladvertising space. Because Bacapres AB operates under the "Change for Improvement" coalition which isconsidered to be in contrast to President Joko Widodo's policies. This research highlights the billboards of twoBacapres, PS and GP, each from a different party, both featuring the same political figure, who comes from oneof the supporting parties. This research aims to see how meaning or discourse is constructed through semioticmodes on the billboards of the two Bacapres. Also examines how the meaning or discourse that is developed iscommunicated to the public so that it can be taken for granted. This research uses Gunter Kress and van Leeuwen'smultimodal discourse approach. The results show that the meaning or discourse in the two billboards of BacapresPS and GP were constructed through a balanced spatial composition and established through carefully designedstages.